A Literature Review on Disciplinary Literacy: How Do Secondary Teachers Apprentice Students Into Mathematical Literacy? - Hillman, Ann Marie (Journal of adolescent & adult literacy, 2014)
Current adolescent literacy rates cause concerns at the number of students who graduate high school with basic or below-basic reading skills. The Common Core State Standards promote disciplinary literacy, which presents advanced literacy skills embedded in content area instruction. Disciplinary literacy is argued as a way to raise adolescent literacy rates. This literature review examines how Discourse theory frames disciplinary literacy as an apprenticeship model, and how instruction in mathematical Discourses focuses on communication and reasoning at the secondary level. Mathematical standards are analyzed for literacy features, and then studies of secondary mathematics classrooms are reviewed in light of these features. The review is offered to help mathematics teachers and literacy specialists build a shared knowledge base of mathematical literacy in secondary classrooms.